The Values of Islamic Education in the Maintenance of Bodies in Surau Gadang Village, Padang City - Putri Irmayanti, Azizah; Kustati, Martin; Amelia, Rezki; Syamsi, Syamsi; Maulana, Febrian (Winter Journal: IMWI Student Research Journal, 2024)
This article discusses the organization of funerals in Surau Gadang Village, Padang City, with a focus on the Islamic education values that guide the process. The organization of a funeral is an integral part of the life of a Muslim community, and in Surau Gadang Village, aspects of Islamic education play a central role in guiding every stage of the process. In this article, the author explains the Islamic education values reflected in the organization of the corpse, including aspects of cleanliness, patience, and social care. Cleanliness is implemented through the process of bathing the corpse (gusul) and using a clean shroud, in accordance with religious guidance. Patience is manifested in the calm and patient attitude of the funeral organizers in facing a process that may be emotionally draining. In addition, social care is reflected in the active participation of the surrounding community in the funeral procession. Kelurahan Surau Gadang promotes the values of solidarity and helping, ensuring that every member of the community feels a sense of care and support in such a difficult moment. Islamic education becomes the main foundation in building these attitudes. This research uses participatory observation and interview methods to document the process of organizing a funeral and analyze the Islamic education values that color every step. The results are expected to make a positive contribution to the understanding and implementation of Islamic education values in everyday life, especially in the context of organizing a funeral in Muslim communities in Surau Gadang Village, Padang City.